Coolness and social vulnerability: Swedish pupils' reflections on participant roles in school bullying. Issue 5 (2nd September 2020) - Strindberg, Joakim; Horton, Paul; Thornberg, Robert
ABSTRACT: The aim of the study was to examine Swedish school pupils' perspectives on why some pupils engage in bullying, support bullying or avoid standing up for the one(s) being bullied, despite a shared understanding that bullying is wrong. Through the use of focus group interviews combined with two bullying vignettes, a total of 74 pupils from grades 5 and 6 (i.e. 11–12 years of age) from two public primary schools in socioeconomically diverse areas were asked for their perspectives on various participant roles in bullying. In interpreting the vignette scenario, the participants emphasised the importance of perceived coolness, as well as the risk of being bullied. In seeking to avoid becoming a 'victim' of bullying, the situational roles of 'bully', 'assistant', 'reinforcer' and 'outsider' were understood as potential means for promoting, maintaining or protecting one's own social position. The findings of the study challenge previous understandings of bullying as an act of harmful or aggressive intentionality and rather highlight the relational and situational aspects of bullying.